Reflexiones sobre el estado de lo urbanístico. Entre la anomalía y la excepción. - JULIO TEJEDOR BIELSA (Revista de Administración Pública, 2010)
The urban planning law has been put under great tensions in last years. Complexes interests that in an economic expansion’s phase are aggravated in general by the pressure of the money are behind this. For that reason, neither the revision’s process of the regime of the ground impelled by the State legislator nor the attention that the European institutions come rendering to Spanish urbanism. In that context, the urban planning law, seem today in deconstruction, submissive deep revision that affects to essential institutions, like the urban planning regime of the property, the classification, the real state appraisal, the regime of the agreements or the regime of execution of the urbanizing work, between some others. In addition, that revision is not limited to the instruments but tries also to reach the contents advocating an urbanism in environmental key, in which, they deeply root the exigencies derived from the sustainable development.